Book review: McNicol, Sarah. Supporting people to live well with dementia: a guide for library services - Elena Maceviciute (Information Research: An International Electronic Journal)
McNicol, Sarah. Supporting people to live well with dementia: a guide for library services. London: Facet Publishing, 2023. xxviii, 182 p. ISBN 978-1-78330-597-1